Surgical technique of retrograde ventricle-sinus shunt is an option for the treatment of hydrocephalus in infants after surgical repair of myelomeningocele - Matheus Fernandes de Oliveira; Manoel Jacobsen Teixeira; Karen Andrade Norremose; Hamilton Matushita; Marcelo de Lima Oliveira; Edson Bor Seng Shu; Fernando Campos Gomes Pinto (Arquivos de Neuro-Psiquiatria)
ABSTRACT Introduction Treatment of hydrocephalus is accomplished primarily through a ventricular-peritoneal shunt (VPS). This study aims to describe the application of retrograde ventricle-sinus shunt (RVSS) in patients with hydrocephalus after surgical treatment of myelomeningocele. Method A prospective, randomized and controlled pilot study. We consecutively enrolled 9 patients with hydrocephalus after surgical repair of myelomeningocele from January 2010 to January 2012. These patients underwent elective RVSS or VPS. Five underwent RVSS and 4 underwent VPS. Patients were followed for one year with quarterly evaluations and application of transcranial Doppler. Results RVSS group showed outcomes similar to those of VPS group. Doppler revealed significant improvement when comparing preoperative to postoperative period. RVSS group had significantly higher cephalic perimeter than VPS group. Neuropsychomotor development, complications and subjective outcomes did not differ between groups. Conclusion RVSS shunt is viable; it is an alternative option for the treatment of hydrocephalus.